TSC22D1 is a newly identified inhibitor of insulin secretion in pancreatic beta cells - Yıldırım, Sümbül; Mhamane, Amit; Lösch, Svenja; Wieder, Annika; Ermis-Kaya, Ezgi; König, Ann-Christine; Yilmaz, Sevgican; Hauck, Stefanie M.; Kocabas, Fatih; Szendrödi, Julia; Herzig, Stephan; Üstünel, Bilgen Ekim (The FEBS journal, 2025)
The loss of pancreatic beta cell function leads to chronically high blood glucose levels, contributing to diabetes mellitus, one of the leading causes of morbidity and mortality worldwide. Understanding the molecular mechanisms that regulate beta cell function could pave the way for the development of more effective antidiabetic treatments. In this study, we identify the evolutionarily conserved transforming growth factor β-1 stimulated clone D1 (TSC22D1) protein as a previously unknown regulator of beta cell function. TSC22D1 depletion in INS-1E cells enhances the expression of key beta cell identity genes, including Ins1, Ins2, Pdx1, Slc2a2, and Nkx6.1, and promotes glucose-stimulated insulin secretion without altering intracellular insulin content. Mechanistically, TSC22D1 and Forkhead box protein O1 (FoxO1) interact and regulate each other in a reciprocal manner to control beta cell function. Our follow-up interactome and RNA-Seq analyses reveal that TSC22D1 is crucial for glucose-responsive cellular processes in beta cells, including mRNA processing, ribonucleoprotein complex biogenesis, and Golgi vesicle transport. Overall, our findings indicate that TSC22D1 plays a significant role in regulating beta cell function at multiple levels, with potential implications for metabolic diseases, such as diabetes.